2017
DOI: 10.1098/rsob.160212
|View full text |Cite
|
Sign up to set email alerts
|

The N -linking glycosylation system from Actinobacillus pleuropneumoniae is required for adhesion and has potential use in glycoengineering

Abstract: Actinobacillus pleuropneumoniae is a mucosal respiratory pathogen causing contagious porcine pleuropneumonia. Pathogenesis studies have demonstrated a major role for the capsule, exotoxins and outer membrane proteins. Actinobacillus pleuropneumoniae can also glycosylate proteins, using a cytoplasmic N-linked glycosylating enzyme designated NGT, but its transcriptional arrangement and role in virulence remains unknown. We investigated the NGT locus and demonstrated that the putative transcriptional unit consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…pleuropneumoniae (Cuccui et al. 2017 ) could also give access to a broader range of hexose ending polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…pleuropneumoniae (Cuccui et al. 2017 ) could also give access to a broader range of hexose ending polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
“… 168 Other studies have developed short, optimized GlycTag sequences for NGT 80 and have shown that the modification of a target protein with these GlycTags (such as GGNWTT) can successfully direct efficient NGT glycosylation of diverse recombinant proteins in vivo and in vitro . 80 , 160 , 173 Later studies have found that the single glucose residue installed by NGT can be elaborated to a dextran polymer 160 (which could be useful for vaccines against pathogenic bacteria that use NGTs to adhere to human cells), polysialic acids 131 (which may prolong the serum-half-life of small therapeutic proteins), N -acetyllactosamine (LacNAc), 174 , 175 and other fucosylated and sialylated forms of lactose 174 , 175 by overexpression of elaborating GTs within the cell. 131 This sequential elaboration technique may also allow an NGT-based system to circumvent the limits on glycan structure found in OST systems.…”
Section: Synthetic Glycosylation Systemsmentioning
confidence: 99%
“…Although HMW1 glycosylates proteins preferably at the consensus sequon Asn -Xxx-Thr/Ser, different amino acids can be tolerated in the third position [ 11 , 14 , 15 ]. Recently, the A. pleuropneumoniae glycosylation operon was used to add N -linked glycan consisting of 1–29 hexose units onto an acceptor protein in E. coli , illustrating the potential biotechnological application of this glycosylation system for glycoengineering [ 16 ].…”
Section: Overview Of Protein Glycosylation In Prokaryotesmentioning
confidence: 99%